ASSIMILATION AND INTEGRATION FOR PRISONERS IN THE MIDDLE OF THE COVID-19 PANDEMIC BASED ON MINISTER OF LAW AND HUMAN RIGHTS REGULATIONS NUMBER 10 OF 2020 - Raymundus Loin; Klara Dawi; Yenny Aman Serah; Didi Haryono; Liza Marina (Journal of Law and Policy Transformation, 2022)
The provision of assimilation and integration programs is one of the answers to the problem of overcrowded prisons . As a result of being overcrowded, prisons cannot implement the health protocol, namely physical distancing recommended by the government. Policies for implementing assimilation programs during the Covid-19 pandemic should be accompanied by legal policies whose impacts can be beneficial for the legal system in Indonesia, especially regarding criminal policies, namely through reconstruction and/or reformulation of the criminal system and criminal sanctions through the application of social work criminal sanctions and prevention and/or or crime prevention through restorative justice efforts and this is taken into consideration as an effort to resolve the over capacity problem.